SOCIÉTÉ DE CLASSE ET PSYCHANALYSE - Claudiu GAIU (Studia Universitatis Babeș-Bolyai. Philosophia)
Class Society and Psychoanalysis. Despite being sidelined, Michel Clouscard was a prolific writer and taught sociology at the Université de Poitiers from 1975 to 1990. Clouscard focused on describing the peculiar discourse of emancipation that resulted from the marriage of psychoanalysis and Marxism, which was then termed Freudo-Marxism, and was gaining currency in the aftermath of May ’68. For Clouscard, the emancipation of desire and productivity upheld by the Freudo-Marxists went hand-in-hand with the emergence of new markets and techno-structures which defined the development of social democracy in France. Two of his works, The Treatise of Mad Love and the Capitalism of Seduction are telling us the story of the birth of class society at the very dawn of Middle Age and his postmodern transformation. The first work is an interpretation of Tristan and Iseul myth. The second describe how the capitalism gave birth to a new category with veritable ferocity: parasitic non-productive jobs (a large category extending from the false artists of modern art to the intellectual sell-outs to the system, passing through publicists and other dealers).